Vernacular design as visual practice of urban space organization - Y. O. Butsykina (Ukrainian Cultural Studies, 2020)
Article discusses specific status of the vernacular design in the visual style of the modern Ukrainian city, where indigenous dwellers coexist with those who came recently from the country. The vernacular regions in Ukrainian cities are analyzed as complex, eclectic and grass-roots. The vernacular design is understood within the complex cultural environment, where different traditions and cultural identities coexist. The terms "vernacular life", "vernacular landscape" are explicated. The vernacular landscape is interpreted in the context of the everyday human activities brought into the public urban spaces. The crucial characteristic (amateur, brutal, trying to be visible and being invisible, economical, tactical, irrational, anachronistic) and the main principles (constraint, thrift, durability, commonness) of the vernacular design are studied within the interpretive context of urban culture collective identity.